Comparison of fetal outcome in spontaneous versus induced labor in postdated pregnancy: a study in a tertiary care centre - Anand, Nikhil; Shah, Hardik (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Pregnancy lasting beyond 40 weeks is a known complication of normal delivery. Various studies have found incidence between 2-14%. Post-dated pregnancy carries specific hazards to both mother and fetus. While mothers are faced with problems like increased incidences of induced labour, instrumental delivery and LSCS with associated morbidities, fetuses are faced with morbidities ranging from IUGR to macrosomia. Authors tried to study fetal outcome in post-dated pregnancy present study. The objective is to compare fetal outcome in spontaneous versus induced labour in post-dated pregnancy. Methods: This is a prospective cross-sectional study done at a tertiary care hospital in obstetrics and gynecology in duration of 18 months. After screening according to inclusion criteria, all patients who were admitted in labour wards are selected and two groups were created according to clinical examination. First group consists of patients with spontaneous onset of labour and second group consists of patients with induction of labour. In each group USG, NST and BPP were performed, and labor monitored according to standard partograph. Fetal outcomes in both groups were studied. Results: Fetal outcomes were nearly same in both groups, induced and spontaneous onset of labour, except a few like thick meconium which was common in spontaneous onset group while rate of LSCS was more in induced group. Conclusions: Women with uncomplicated pregnancies should be offered induction of labour, while women with any complicating factors LSCS should be considered.